Leprosy frequency in the world, 1999-2010 - Penna, Maria Lúcia Fernandes (2012)
In 1991, the World Health Organization (WHO) committed to reducing the prevalence of leprosy to below 1 in 10,000 inhabitants by 2000. Significant improvements in leprosy control have occurred, but leprosy remains a public health problem in many countries due to its high incidence and rate of transmission. This paper reviews data published by the WHO in the years 2000, 2005 and 2010. These data sets included 148 countries or territories that reported to the WHO at least once. Only four countries reported higher prevalence rates in 2010 than in 2000 and eight reported higher case detection rate (CDR) in 2009 than in 1999. Prevalence rate reductions were greater for the first five-year period examined, while CDR reductions were greater in the second five-year period. Thirty-six countries and territories reported at least one prevalence value higher than 1 per 10,000 inhabitants and 32 reported at least one CDR value higher than 9 per 100,000 inhabitants. A total of 39 countries fit at least one of these criteria and all were located in tropical regions.